Verbal creativity in autism: comprehension and generation of metaphoric language in high-functioning autism spectrum disorder and typical development - Kasirer, Anat; Mashal, Nira (Frontiers in Human Neuroscience, 2014)
Studies on creativity in participants with autism generally show impoverished performance as well as deficient comprehension of metaphoric language. However, very little is known about the ability to generate metaphors in this population. The present study examines verbal creativity in adults with autism-spectrum disorder (ASD) through tasks that rely on novel metaphoric language. Seventeen adults with ASD (mean age = 21.06) and 17 typically developing peers (mean age = 22.71) participated in the study. A multiple-choice questionnaire consisting of conventional and novel metaphors was used to test comprehension, and a sentence completion questionnaire was used to test generation of creative language. Results show similar performance in comprehension of conventional and novel metaphors in both groups, whereas adults with ASD generated more creative metaphors relative to the control group. Scores on tests of vocabulary and naming contributed to the prediction of conventional metaphor comprehension, while scores on tests of mental flexibility contributed to the prediction of novel metaphor comprehension. In addition, scores on a test of non-verbal intelligence contributed to the prediction of metaphor generation. The study points to unique verbal creativity in ASD.